MODIFICATION OF DNA ISOLATION PROTOCOL FROM SILICA GEL DRIED-LEAF TISSUES OF Pinanga (PALMAE) - Joko Ridho Witono; Katsuhiko Kondo (Research Center for Biology-Indonesian Institute of Sciences, 2006)
DNA isolation is an important issue in molecular fields especially for specific plant group such as Pinanga (Palmae). Typically,leaflets structure of Pinanga consists of shiny leaflets as common species of palms and mottled leaflets. Pinanga javana and P.coronata form commonly the two types of leaflets. The high quality of DNA of Pinanga with the shiny leaflet is readily purified and that with the mottled leaflet needed DNA purification due to the presence of high polyphenolic compound. Application of the silica binding method was recommended to purify the template DNA. Modified DNA-isolation protocol is relatively quick, simple,least expensive, minimum equipments and chemicals required, and suitable for PCR and endonucleases digestion reaction.